Severe Symptomatic Hypophosphataemia as a Complication of Parenteral Iron Replacement - Teh, Kevin Kim-Jun (Eur J Case Rep Intern Med, 2020)
Parental iron replacement is given to patients with severe iron deficiency or intolerance to oral iron. Hypophosphataemia has been reported to occur as a complication of parental iron replacement, and is postulated to be related to the carbohydrate moieties used in the parenteral preparations. Hypophosphataemia is under-diagnosed as symptoms such as fatigue, muscle weakness and poor effort tolerance mimic anaemia. Severe hypophosphataemia (<0.32 mmol/l) can result in significant complications such as confusion, rhabdomyolysis and arrhythmias. We report a patient with recurrent admissions for non-specific symptoms attributed to iron deficiency anaemia who received multiple doses of parenteral ferric carboxymaltose (FCM). He was found to have severe hypophosphataemia, with further evaluation showing increased renal phosphate wasting and elevated serum levels of fibroblast-growth-factor 23 (FGF23). FCM was stopped and he was given high-dose oral iron supplementation, with no further episodes of hypophosphataemia. LEARNING POINTS: The carbohydrate moieties used in parenteral iron preparations are different, and may have a dose-dependent relationship with the development of hypophosphataemia. The mechanism by which hypophosphataemia occurs after parenteral iron replacement is related to increased serum levels of FGF23, which increases renal phosphate wasting. The serum phosphate levels of patients receiving parenteral iron replacement (especially ferric carboxymaltose or iron polymaltose) should be routinely monitored for hypophosphataemia, which is an under-diagnosed complication.